MAKNA PRINSIP KEHATI-HATIAN DALAM PERATURAN DAERAH RENCANA TATA RUANG WILAYAH BERBASIS KEBERLANJUTAN LINGKUNGAN HIDUP DI PROVINSI MALUKU - Angga, La Ode (Jurnal Media Hukum, 2017)
Precautionary Principles in the protection and environmental management in the field of RTRW in Maluku Province on Regional Regulation No. 16 of 2013 on RTRW is a law regulating the livelihood of Maluku people in the field of spatial plan which aims to create a spatial that can give birth to the welfare of the community in the spatial area. In order to minimize the occurrence of conflicts or disputes that occur in the field of arrangement space in Maluku Province. Welfare State Theory of the provincial government should take a role in the formation of the RTRW law. Provincial RTRW of Maluku Law does not mention the Precautionary Principles because: a. Philosophical Aspects, Perda RTRW No. 16 of 2013 does not inspire or reflect Article 2f of UUPPLH-2009 and Article 55-59 of UUPR as the higher Law in Spatial Planning in Indonesia; b. Juridical Aspects The existence of the synchronization of laws and regulations, particularly the Regional Regulation on RTRW of Maluku Province No. 16 of Â 2013-2033 with UUPPLH-2009 where in the RTRW regulation there is no Precautionary Principles regulation, whereas in UUPPLH-2009 itself has set clear and precise regulation of prudential principles Article 2f and Article 44; c. Political Aspects The existence of unclear orientation of political vision for the forming of Perda RTRW No. 16 of 2013, on the other hand the Provincial RTRW Law of Maluku based on environmental sustainability but there is no Precautionary Â Principles regulation.